Randomised controlled trial examining the effect of an outpatient exercise training programme on haemodynamics and cardiac MR parameters of right ventricular function in patients with pulmonary arterial hypertension: the ExPAH study protocol. Issue 2 (6th February 2017) - Chia, Karen S W; Faux, Steven G; Wong, Peter K K; Holloway, Cameron; Assareh, Hassan; McLachlan, Craig S; Kotlyar, Eugene
Abstract : Introduction: Pulmonary hypertension (PH) is a potentially life-threatening condition characterised by elevated pulmonary artery pressure. Early stage PH patients are often asymptomatic. Disease progression is associated with impairment of right ventricular function and progressive dyspnoea. Current guidelines recommend exercise training (grade IIa, level B). However, many questions remain regarding the mechanisms of improvement, intensity of supervision and optimal frequency, duration and intensity of exercise. This study will assess the effect of an outpatient rehabilitation programme on haemodynamics and cardiac right ventricular function in patients with pulmonary arterial hypertension (PAH), a subgroup of PH. Methods and analysis: This randomised controlled trial involves both a major urban tertiary and smaller regional hospital in New South Wales, Australia. The intervention will compare an outpatient rehabilitation programme with a control group (home exercise programme). Participants will be stable on oral PAH-specific therapy. The primary outcome measure will be right ventricular ejection fraction measured by cardiac MRI. Secondary outcomes will include haemodynamics measured by right heart catheterisation, endurance, functional capacity, health-related quality of life questionnaires and biomarkers of cardiac function and inflammation. Ethics approval and dissemination: Ethical approval has been granted by St Vincent's Hospital, Sydney (HREC/14/SVH/341). Results of this study will be disseminated through presentation at scientific conferences and in scientific journals. Trial registration number: ACTRN12615001041549; pre-results.